MULTIPLIKASI TUNAS EKSPLAN BUAH NAGA DENGAN PENAMBAHAN EKSTRAK PISANG AMBON SECARA IN VITRO - Cahya, Nur; Asnawati, Asnawati; Budi, Setia (Agros Journal of Agriculture Science, 2024)
Dragon fruit is an agricultural product that has been grown commercially for a long time and yields outstanding commodities with a reasonably high economic worth. The demand for dragon fruit is growing year, necessitating the continuous supply of premium seeds in substantial amounts. By employing in vitro culture to multiply them, dragon fruit seeds may be made more readily available. In order to maximize the in vitro growth of dragon fruit shoots, this study attempts to determine the optimal dosage of Ambon banana extract. For four months, the study was carried out at Tanjungpura University's Biotechnology Laboratory. This study employed a totally randomized design with one component that included seven treatment levels: six concentration levels of Ambon banana extract and MS medium as a control. Each treatment included four experimental plants and four replications, for a total of 112 plants. Ambon banana extract concentration, n0 = 0, n1 = 25 g/l, n2 = 50 g/l, n3 = 75 g/l, n4 = 100 g/l, n5 = 125 g/l, and n6 = 150 g/l The time of shoot emergence, number of shoots, time of root emergence, number of roots, and shot % were the variables that were observed. This study employed a totally randomized design with one component that included seven treatment levels: six concentration levels of Ambon banana extract and MS medium as a control. Each treatment included four experimental plants and four replications, for a total of 112 plants. Ambon banana extract concentration, n0 = 0, n1 = 25 g/l, n2 = 50 g/l, n3 = 75 g/l, n4 = 100 g/l, n5 = 125 g/l, and n6 = 150 g/l The time of shoot emergence, number of shoots, time of root emergence, number of roots, and shot % were the variables that were observed. Keywords: dragon fruit, concentration, ambon banana extract,  MS media,    multiplication. INTISARIBuah naga merupakan tanaman pertanian yang menghasilkan komoditi unggulan dengan nilai ekonomi yang relatif tinggi dan telah dibudidayakan secara komersial sejak lama. Permintaan buah naga  terus meningkat setiap tahunnya sehingga memerlukan ketersediaan benih berkualitas tinggi dalam jumlah banyak secara berkelanjutan. Permasalahan ketersediaan bibit buah naga dapat diatasi dengan memperbanyak secara kultur in vitro. Penelitian ini bertujuan untuk mendapatkan konsentrasi ekstrak pisang ambon terbaik untuk memperoleh multiplikasi tunas buah naga terbanyak secara in vitro. Penelitian dilakukan di Laboratorium Bioteknologi  Universitas Tanjungpura selama 4 bulan. Penelitian ini menggunakan rancangan acak lengkap satu faktor yang terdiri dari 7 taraf perlakuan yaitu media MS sebagai kontrol dan 6 taraf konsentrasi ekstrak pisang ambon, masing-masing perlakuan mempunyai 4 ulangan dan 4 tanaman percobaan, sehingga jumlah tanaman sebanyak 112 tanaman. 112. Konsentrasi ekstrak pisang ambon, n0= 0, n1= 25 g/l, n2= 50 g/l, n3= 75 g/l, n4= 100 g/l, n5= 125 g/l, n6= 150 g /l Variabel yang diamati adalah waktu munculnya tunas, jumlah tunas, waktu munculnya akar, jumlah akar dan persentase tunas. Hasil penelitian menunjukkan bahwa penambahan ekstrak pisang ambon pada media 1/2 MS  konsentrasi 100 g/L memberikan hasil paling efektif dalam kultur in vitro buah naga pada variable presentase bertunas. Kata Kunci: Buah Naga, Konsentrasi, Ekstrak Pisang Ambon, Media MS, Multiplikasi